1995
DOI: 10.1139/y95-724
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of brown adipose tissue activity in tumor-bearing rats

Abstract: Despite anorexia, cancer development is frequently accompanied by an increase of energy expenditure. Considering the pivotal role played by brown adipose tissue (BAT) in the energy metabolism of small mammals, we investigated the functional and compositional modification in BAT of anorexic tumor-bearing (Yoshida sarcoma) and pair-fed control rats. BAT thermogenic activity (assessed by maximal mitochondrial GDP binding) was 1.8-fold greater in tumor-bearing rats than in controls, while the thermogenic capacity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…In addition, during cachexia there is an important energetic imbalance. An increase in BAT thermogenesis has been described both in humans [16] and experimental animals [17]. Therefore, non-shivering thermogenesis due to either BAT activity or muscle increased thermogenesis (as suggested here) may be very important factors contributing to the decreased energy e¤ciency found in the cachectic state.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…In addition, during cachexia there is an important energetic imbalance. An increase in BAT thermogenesis has been described both in humans [16] and experimental animals [17]. Therefore, non-shivering thermogenesis due to either BAT activity or muscle increased thermogenesis (as suggested here) may be very important factors contributing to the decreased energy e¤ciency found in the cachectic state.…”
Section: Resultssupporting
confidence: 54%
“…Since cachexia tends to develop at a rather advanced stage of the neoplastic growth, preventing muscle waste in cancer patients is of a great potential clinical interest. Previous studies (See [15] for review) have shown that during cachectic states there is an increase in BAT thermogenesis both in humans [16] and experimental animals [17]. In addition, Roe et al [18] have shown that there is an increased oxygen consumption in leukaemic rats.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Increased thermogenic activity of BAT, as assessed by GDP binding, has been demonstrated in cancer cachexia models. 21,22 Our results suggested that inappropriate increased energy expenditure in BAT was associated with uremia-associated cachexia. Elevated BAT UCP-1 expression was attenuated by NBI-12i treatment.…”
Section: Discussionmentioning
confidence: 64%
“…Increased energy expenditure, which has been reported in both human and rodents with cancer cachexia (Hyltander et al . 1991; Oudart et al . 1995; Roe et al .…”
Section: Discussionmentioning
confidence: 99%